If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 4) = (5x + 2) Reorder the terms: (4 + 8x) = (5x + 2) Remove parenthesis around (4 + 8x) 4 + 8x = (5x + 2) Reorder the terms: 4 + 8x = (2 + 5x) Remove parenthesis around (2 + 5x) 4 + 8x = 2 + 5x Solving 4 + 8x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 4 + 8x + -5x = 2 + 5x + -5x Combine like terms: 8x + -5x = 3x 4 + 3x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 4 + 3x = 2 + 0 4 + 3x = 2 Add '-4' to each side of the equation. 4 + -4 + 3x = 2 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 2 + -4 3x = 2 + -4 Combine like terms: 2 + -4 = -2 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| Sinx=0.75 | | 2a+16+b=18+b | | 9x+26x^2=3 | | 6y-2=2y+7 | | 8+3x+x=20 | | 58474+46274= | | t=5(2)+3(4) | | 15-3x+2-8x=39 | | 58584839748375097+85574758475398= | | 7x-5y+(-3x+-4y)= | | M(m+2)=2 | | 5x-13=-25 | | 13y^2-4y-9=0 | | 4w=w-2 | | 13y^2-4y+9=0 | | x^2+y^2=4x-4y-6 | | 40+7x=0 | | 0.3*x+x^2=0.3x^3 | | (3c-2)(2c+5)=0 | | x^2+y^2-4x+4y+6=0 | | (45x^6)-(36y^2)-144=0 | | (45x^2)-(36x^2)-144=0 | | (36x^2)+(36x^2)-144=0 | | 4v-3=-5 | | (y^2-6)+(90)+(y+1)=180 | | 13x-10+12x=180 | | (10y^2)+(y^2-6)+(y+1)=180 | | 15(-1/6)n=(1/6)n-1 | | 2x-6x+42=0 | | (5y-5)=(2y+2) | | 5y-5=2y+2 | | x^2=6.3125 |